2013
DOI: 10.1177/1359105312470853
|View full text |Cite
|
Sign up to set email alerts
|

Illness representations of type 2 diabetes patients are associated with perceptions of diabetes threat in relatives

Abstract: In the fight against the type 2 diabetes epidemic, patients might be asked to discuss familial susceptibility to type 2 diabetes in their family. Illness representations of patients (N = 546) were assessed to explore their impact on perceived type 2 diabetes threat in relatives. Reporting high type 2 diabetes burden, emotional impact and perceiving type 2 diabetes as an inheritable disease seemed to increase patients' family risk perception and worries about relatives' future health. Patients with coherent ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The results from the quantitative studies show that patients did not report major consequences of type 2 diabetes (IPQ-R: M score= 16.23 [33]; M=2.49, [39]; M=2.49, [36]). One study showed that the recollections of family members' social and general consequences of type 2 diabetes were associated with patients' own representations of social and general consequences (p=.01 and p=05 respectively) [38].…”
Section: Consequencesmentioning
confidence: 92%
See 3 more Smart Citations
“…The results from the quantitative studies show that patients did not report major consequences of type 2 diabetes (IPQ-R: M score= 16.23 [33]; M=2.49, [39]; M=2.49, [36]). One study showed that the recollections of family members' social and general consequences of type 2 diabetes were associated with patients' own representations of social and general consequences (p=.01 and p=05 respectively) [38].…”
Section: Consequencesmentioning
confidence: 92%
“…Eight studies explored patients' perceptions of type 2 diabetes timeline and showed mixed results [14,16,18,25,32,33,36,39]. The majority of patients in six of the studies believed that type 2 diabetes is permanent and life-long [16,18,25,33,36,39]. Fifty percent of the patients in one study said that type 2 diabetes is a long term condition but some people expected it to be cured [14].…”
Section: Timelinementioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of familial risk perception of diabetes threat in relatives, van Esch et al (2013) reported that patients with coherent illness understanding reported positive beliefs regarding type 2 diabetes prevention in relatives. They also reported the presence of subgroups (e.g., those with high disease burden) that had elevated family risk perception.…”
Section: Discussionmentioning
confidence: 99%